Kewenangan Badan Pengawas Pemilu Berdasarkan Peraturan Perundang-Undangan - Pelu, Handika Dwi Ardiansyah; Silubun, Yosman Leonard (Jurnal Restorative Justice, 2025)
The institutional capacity of Bawaslu as a dispute resolver, starting from the personal commissioner of Bawaslu who has a strong vision regarding the design of dispute resolution as well as the carrying capacity of an organization that is capable of operationalizing its authority. Bawaslu itself has been strengthened by the existing electoral legal system, of course there are still various evaluations in strengthening the Bawaslu institution in order to achieve general elections that are not only democratic but also have integrity. This research aims to determine the Authority of the Election Supervisory Body Based on Legislative Mechanisms. In line with the problems to be researched, this research includes normative legal research using a Normative Juridical approach which takes primary data by conducting a literature review and secondary data by processing it from legal materials. primary, secondary legal materials, and tertiary legal materials. Bawaslu's authority in accordance with law number 7 of 2017 concerning general elections is weak, the existence of Bawaslu in previous elections seems to have been limited to "complementary" because the authority given to this institution was inadequate in contributing to upholding election justice.